Analisis faktor-faktor yang mempengaruhi bayaran take home pay anggota koperasi Agro Niaga Jabung Syariah Jawa Timur - Zakiya, Lutfa Rahma; Maharani, Dian (Maliki Interdisciplinary Journal, 2023)
Efficiency dairy cattle business in Indonesia is low due to the dominance of small-scale businesses which account for 80% of the total dairy business in Indonesia, The goal of developing the dairy cattle industry in the livestock sector is to increase milk production as well as to create more jobs and increase farmers’ income. In Indonesia, cooperatives are home to the majority of farmers, research was conducted to find the factors that affect the Take Home Pay (THP) of dairy farmers who are members of the KAN Jabung. Multiple linear regression analysis research method will be used with 100 samples selected using purposive random sampling. Based on the p-value of the F test statistics obtained a value of 2.2e-16α. conclusion obtained that the length of farming, the age of the farmer, the number of mothers, and milk production per mother have a significant effect on the THP received by farmers. Every increase of 1 value of length of farming, THP decrease by IDR 10,877.00. Every increase of 1 breeder age value, THP decrease by Rp3,220. Every increase of 1 mother, THP increase by Rp228,535.00. Every increase of 1 milk production value per mother, THP increase by Rp74,504.00.